Six years of following up a glomus jugulare tumor - a case report - Ivanka Štenc Bradvica; Davor Jančuljak; Silva Butković-Soldo; Ivan Hećimović (Medicinski Glasnik, 2012)
This case report followed up a patient for six years after she had been successfully treated by embolization and gamma knife surgery, while a complete surgical resection was contraindicated because of the high risk of possible mortality outcome. A development of internal hydrocephalus in a subacute postoperative period as a probable postoperative complication related to gamma knife surgery was noted.